If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(-1) + 2y = 0 Multiply 2 * -1 -2 + 2y = 0 Solving -2 + 2y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + 2y = 0 + 2 Combine like terms: -2 + 2 = 0 0 + 2y = 0 + 2 2y = 0 + 2 Combine like terms: 0 + 2 = 2 2y = 2 Divide each side by '2'. y = 1 Simplifying y = 1
| .2x-2=.667x-.4x | | 2x^2-4x=2x^2+9x-72 | | 5(4-x)=-10x | | 7(3-k)=-3k+21 | | -4(x+1)+5x=11 | | -2x+0=2 | | 0.10(x+70)+0.70x=23 | | -10x+1=5 | | X(2x-4)=(2x+9)(x-8) | | -(8y+3)-(-7y-6)=2 | | x+1+7x+55=2x-1 | | (5x+4)=(8x-3) | | -14u+2u+16u=-12 | | 2(-2x-y)=2(1) | | y^4-36y^2=-35 | | 2x+3(3x-4)=21 | | -2p+5p=3-21 | | X(2x-4)=(2x+8)(x-8) | | 56t^2-23t-63=0 | | 5(4-x)=-10 | | s^3+16s^2+64s=0 | | 6x^2+35x+25= | | 3x(a-3)-5(3-a)=0 | | 7x+3=-36 | | (x)(3x-y)(4x+5y)= | | 3x+7=-36 | | 8x-5=7-4x | | x/3-4=7 | | x(3x-y)(4x+5y)= | | -17+11+6=7t | | 2x+8=-48 | | 7xy^4-7xy^2=0 |